Design of a Pedagogical Gamification Tool for Improving Interaction in Online EFL Education, in the province of Imbabura - Mina Vásquez, Iván Mateo; Viveros Almeida , Martha Aracelly; Mina Ortega, Marcelo René (Arandu UTIC, 2025)
The research was based on a qualitative, bibliographic-documentary approach, through a systematic review of national and international literature, analysis of regulatory frameworks, and identification of trends on teacher training platforms such as Mecapacito. The results show that gamification significantly contributes to students’ motivation, autonomy, and participation in virtual environments, as well as fostering interaction and reducing language anxiety. The guide integrates pedagogical foundations, gamified elements (such as badges, progression, rankings, and immediate feedback), and accessible digital tools for teaching practice. It also aligns with active methodologies included in Ecuador’s teacher training curricula, such as Problem-Based Learning, Flipped Classroom, CLT, TBLT, and Project-Based Learning. In conclusion, the guide constitutes a practical contribution to the educational field by providing teachers with clear, contextualized resources that strengthen online English instruction thru playful and innovative strategies. Its relevance is grounded in the Ecuadorian pedagogical, legal, and curricular framework, which ensures its applicability and relevance in current teacher training.